TRANSLATION METHODS OF COMPLAINT UTTERANCE IN DESCENDANTS FILM DIRECTED ALEXANDER PAYNE - Euis Meinawati (Wanastra: Jurnal Bahasa dan Sastra, 2014)
The title of this research is about the translation problem on translating complaint expressions in the film Descendants. The purpose of this research is to find the problems which shown when the translator uses one of the method in translation. The theory which is used in the analysis is the translation theory by Newmark. The data of this analysis is taken from film Descendants in twoversions that are English and Indonesian Version. There are 12 data which consist of complaint utterances from male characters. The conclusion of this research is complaint utterances which mostly used statement, there are 4 complaint utterances which is translated uses semantic translation method. Because the translator wants to hold the meaning based on the context of story and originality.